An analysis the relationship between IT-business strategic alignment and intangible IT resources on the competitive advantages sustainability moderating effect of IT personnel capability - Lahcene, Makhloufi; Abu Al-Rejal, Hussein Mohammed Esmail; Mohtar, Shahimi (AESS Publication, 2018)
Understanding the relationship between IT Business Strategic Alignment (ITBSA), IT Personnel Capabilities (ITPC), and Intangible IT Resources (IITR) is utmost important. Strategic scholars and professionals look to these three strategic resources as the main driver of generating distinctive competencies which in turn becomes the main source for creating sustainable competitive advantages (SCA). The aim of this study is to establish and understand a new path between three strategic inputs on the SCA which overlooked in the literature and cover this critical gap. The main objective of this paper is to determine whether IT personnel capability will influence directly and indirectly (moderating role) on the relationship between IT business strategic alignment and intangible IT resources towards creating SCA. Hence, this paper question to what extent capability of IT personnel is able to strengthen the relationship between ITBSA and ITPC on the SCA. Applying, Resources-based View (RBV) and Dynamic Capability View (DCV), this paper intend to investigate the role of IT personnel capability on enabling firm’s strategic resources such as ITBSA and IITR toward creating SCA. Therefore, in order to achieve the proposed objectives and answering the questions of this study, the author will apply cross sectional survey for collection appropriate data from IT managers among Algerian high-tech industry. Findings, implications and suggestions will be discussed.